Blood brothers and peace pipes : performing the Wild West in German festivals - Weber, Alina Dana (Folklore studies in a multicultural world., 2019)
The first academic book-length study devoted to Karl May festivals, a specific type of Wild-West-themed festivals that take place in Germany every summer, Blood Brothers and Peace Pipes introduces readers to a performance world that is popular at home yet virtually unknown elsewhere. Named for Karl May (1842-1912), arguably the most famous German writer of adventure fiction in the nineteenth and twentieth centuries, these thirteen or so festivals dramatize the exploits of May's most famous Wild West heroes, the Mescalero Apache Winnetou and his blood-brother, the German frontiersman Old Shatterhand, in entertaining theatre plays that use horses, other animals, stunts, and special effects on outdoors stages built specifically for them. Based on ethnographic studies of six of these events, Weber explores the most fundamental features of Karl May festivals: their "Indian" iconographies, fraternity narratives, hybrid genre form, borrowings from U.S. Wild West shows, and performative diversity. Her narrative accounts of these festivals and their interdisciplinary analysis based on German literature and culture studies, folklore, ethnography, and performance studies, theatre studies, and history guide readers through a specifically German performance world that is not an upshot of the American western, but a homegrown, traditional German version that evolved parallel with it. The composite image of Karl May festivals that emerges in the course of Weber's analysis is that of a unique type of popular event that expresses a deep yearning in German society, that for egalitarian and respectful cross-cultural interactions